1997
DOI: 10.1002/(sici)1097-4636(199705)35:2<147::aid-jbm2>3.3.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Degradation potential of biological tissues fixed with various fixatives: An in vitro study

Abstract: Abstract:The purpose of this study was to investigate the its helical integrity. This made penetration of enzymes into in vitro degradation potential of porcine pericardia fixed with biological tissue easier. Of the multifunctional EC test groups, various aldehyde or epoxy compound (EC) fixatives, using tissues fixed with tetrafunctional EC (EX-521) or trifunctional bacterial collagenase and pronase. The fixatives investigated EC (EX-313) had relatively better resistance to degradation were formaldehyde (FA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 2 publications
0
17
0
1
Order By: Relevance
“…This is mostly due to inflammatory and cytotoxicity changes (Huang , and continuous wear and tear leading to collagen fiber fragmentation. Besides glutaraldehyde, several cross-linking compounds have been reported in the literature such as genipin (Wei et al, 2005) or epoxy compound (Sung et al, 1997). These alternative methods are used to bridge hydroxylysine residues of different polypeptide chains or amino groups of lysine by oligomeric or monomeric crosslinks (Sung et al, 2003).…”
Section: Cross-linking Treatment Of Pericardial Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…This is mostly due to inflammatory and cytotoxicity changes (Huang , and continuous wear and tear leading to collagen fiber fragmentation. Besides glutaraldehyde, several cross-linking compounds have been reported in the literature such as genipin (Wei et al, 2005) or epoxy compound (Sung et al, 1997). These alternative methods are used to bridge hydroxylysine residues of different polypeptide chains or amino groups of lysine by oligomeric or monomeric crosslinks (Sung et al, 2003).…”
Section: Cross-linking Treatment Of Pericardial Tissuementioning
confidence: 99%
“…Because of the adverse effects of cross-linking with glutaraldehyde or other aldehyde treatments such as formaldehyde (Nimni et al, 1988) or dialdehyde starch (Rosenberg, 1978), numerous non-aldehyde treatments have been proposed, such as carbodiimides (Sung et al, 2003), glycerol (Ferrans et al, 1991), glycidal ethers (Thyagarajanet al, 1992) including poly(glycidylether) (Noishiki et al, 1986), acyl azide (Petite et al, 1990), cyanimide (Pereira et al, 1990), genipin (Wei et al, 2005), or dye-mediated photo-oxidation, phytate (Grases et al, 2008). Genipin, obtained from the fruits of Gardenia jasminoides ELLIS (Fujikawa et al, 1987;Tsai et al, 1994), exhibited better results than glutaraldehyde regarding its cytotoxicity (Sung et al, 1999), inflammatory response, ability to prevent calcification and tissue-induced mechanical properties (Wei et al, 2005 , 1989), was shown to be less cytotoxic, superior in pliability and to better inhibit calcification than glutaraldehyde (Sung et al, 1997). Carbodiimides generate amide-type crosslinks via direct cross-linking of the polypeptide chains.…”
Section: Cross-linking Treatment Of Pericardial Tissuementioning
confidence: 99%
“…[5][6][7] However, the crosslinked product has been associated with local cytotoxicity and, more importantly, severe calcification of the material that can over time lead to subsequent matrix deterioration and compromised mechanical properties. [8][9][10] The detailed pathways controlling calcification of cardiovascular tissue, both natural and prosthetic, are not explicitly understood, but as the most common pathology recorded in heart valve failures, 11,12 it is certainly a process under high investigation. It is observed that chemically crosslinking pericardium damages and distorts the natural structure, destroys interstitial cells, and diminishes potential for viable cell inhabitation.…”
mentioning
confidence: 99%
“…In one theory, responding immune cells are reported to secrete collagenase, among other proteolytic enzymes, which immediately begins to degrade the collagen network. 9 It is further hypothesized by some that this initial proteolysis of crosslinked collagen debris creates foci for calcium deposition to initialize. 1,10,16 Studies have shown a cooperative relationship between calcification of this type of tissue and the inflammatory response, enzymatic degradation, and microstructural failure (both independent failures and those associated with calcium deposits.…”
mentioning
confidence: 99%
“…Local distortion of triple-helix and macromolecular packing is due to the side branches created by reaction of the (hydroxy) lysine residues with aldehyde groups [53]. Cross-links are thought to push adjacent molecules apart in the closely packed overlap regions of the fibrils and to cause the expansion of the collagen network [54].…”
Section: Discussionmentioning
confidence: 99%